KORELASI ANTARA AKTIVITAS DALAM BERORGANISASI MAHASISWA DENGAN PRESTASI AKADEMIK ( STUDI KASUS PIMPINAN KELEMBAGAAN FISIP UNIVERSITAS RIAU PERIODE 2014-2015 ) - Yaslan, Muhammad; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was conducted at the University of Riau precisely faculty of social science and politics and partly in existence a former activist college student that has been the graduation of his and has worked. With fact the formulation of a problem: (1) how characteristics a college student who is active in and outcast the the University of Riau organizational ? (2) factors other than a fuel whatever thing you people have become motivation of the creation was what the students are active in the structure of students in and outcast the the University of Riau ? (3) how show any correlations between of activity in become an ordinary organization a student with academic performance of a student at a and outcast the ? For the purpose of this research is to know (1) characteristic students active in organize (activist) and university in riau . (2) to capture a motivation students organizations active in university of Riau . (3) to know the correlation between activity in organize student (activist) with student academic performance. This study used the descriptive quantitative research .By using the method the sample collection by the census .Of factors affect the students active in organization consisting of internal and external factors .Relationship or a correlation between activity in (activist) in organization and UR , performing achievment was in 0.739 (73.9 %) , with a significantly by 0.000 , smaller than 0.05 significant , which means there is the relationship between activity in organize (activist) with academic performance .Keywords: organization, activist, achievement